Perlindungan Hukum Terhadap Pemegang Saham Minoritas Atas Akuisisi Perseroan Terbatas - Aditya Prayoga; Muskibah Muskibah (Universitas Jambi, Fakultas Hukum, 2020)
This study discusses the rights of shareholders namely minority shareholders over the acquisition of a Limited Liability Company based on Company law. This study aims to determine and analyze how the form of legal protection for minority shareholders in the event of the acquisition of a Limited Liability Company by analyzing the judge's judgment in deciding Case No. 1102 K / Pdt / 2015 is associated with applicable laws and regulations. The research method used is normative juridical, using the statutory approach, conceptual approach, and case approach. The results showed that the legal protection arrangements for minority shareholders on the acquisition of Limited Liability Companies are contained in Article 61 and 62 of the Company Law, but according to Article 126 paragraph (1) states that the acquisition process must pay attention to the interests of minority shareholders, while in Article 126 paragraph (3) , the shareholders' disapproval of the acquisition requesting that the shares be repurchased by the Company (Article 62 of the Company Law) does not stop the acquisition. Judge's consideration in deciding case No. 1102 K / Pdt / 2015, philosophically is a minority shareholder in Legal Standing, that is, it should be a minority shareholder in the Company which is sued not as a Director in the Company itself, its juridical consideration is based on the provisions of the applicable legislation, while its sociological considerations are based on the benefit obtained from the parties to the decision. Keywords: Legal; Protection; Acquisitions AbstrakPenelitian ini membahas hak pemegang saham yaitu pemegang saham minoritas atas akuisisi Perseroan Terbatas berdasarkan hukum Perseroan. Penelitian ini bertujuan untuk mengetahui dan menganalisis bagaimana bentuk perlindungan hukum terhadap pemegang saham minoritas dalam hal terjadinya akuisisi Perseroan Terbatas berdasarkan Perundang-Undangan yang berlaku. Metode penelitian yang digunakan adalah yuridis normatif, dengan menggunakan pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan kasus. Hasil penelitian menunjukan, bentuk perlindungan hukum terhadap pemegang saham minoritas berdasarkan Pasal 61 dan 62 Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas adalah hak untuk mengajukan gugatan dan hak untuk meminta sahamnya dibeli oleh perseroan dalam hal pemegang saham tidak menyetujui tindakan perseroan yang merugikan pemegang saham, dan pertimbangan hakim dalam memutus Perkara Nomor 32/Pdt.G/2017 Pengadilan Negeri Palangka Raya, telah sesuai dengan Peraturan Perundang-Undangan yang berlaku, karena dalil gugatannya merupakan penggabungan gugatan antara Perbuatan Melawan Hukum dan Wanprestasi dan bertentangan dengan hukum acara sehingga mengandung cacat formil dan kabur (obscuur libel). Kata Kunci: Perlindungan; Hukum; Akuisisi